2000
DOI: 10.2307/3284907
|View full text |Cite
|
Sign up to set email alerts
|

A Light Microscopy Study of the Migration of Naegleria fowleri from the Nasal Submucosa to the Central Nervous System during the Early Stage of Primary Amebic Meningoencephalitis in Mice

Abstract: The migratory pathway of Naegleria fowleri from the nasal submucosa to the central nervous system (CNS) during the early stage of primary amebic meningoencephalitis (PAM) was investigated in mice. Twenty-one-day-old CD-1 mice were inoculated by intranasal instillation of 1 x 10(6) amebas. Animals were divided into 3 groups of 5 and, after being anesthetized, were killed at intervals of 24, 32, and 48 hr postinoculation by transcardial perfusion with formaldehyde, acetic acid, and methanol. The heads were decal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 0 publications
3
52
0
Order By: Relevance
“…These results confirmed previous experiments with BSM and PSM, and showed that the mucin MUC5AC may be an important protective barrier, reducing adhesion and cytotoxicity to the airway epithelium. Histopathological studies using a murine model have shown that this amoeba infects its host by invading the olfactory mucosa, migrating through the olfactory nerves, crossing the cribiform plate, and entering the olfactory bulbs (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002. At the very early stages of infection, trophozoites are observed at the lumen of the nasal cavity embedded in mucus secretions (Rojas-Hernández et al, 2004).…”
Section: Nci-h292 Cells and Muc5ac Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirmed previous experiments with BSM and PSM, and showed that the mucin MUC5AC may be an important protective barrier, reducing adhesion and cytotoxicity to the airway epithelium. Histopathological studies using a murine model have shown that this amoeba infects its host by invading the olfactory mucosa, migrating through the olfactory nerves, crossing the cribiform plate, and entering the olfactory bulbs (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002. At the very early stages of infection, trophozoites are observed at the lumen of the nasal cavity embedded in mucus secretions (Rojas-Hernández et al, 2004).…”
Section: Nci-h292 Cells and Muc5ac Assaysmentioning
confidence: 99%
“…It has been demonstrated that this protozoan gains access to the CNS by penetrating the olfactory neuroepithelium and invading the olfactory bulbs (Carter, 1970;Jarolim et al, 2000Jarolim et al, , 2002Rojas-Hernández et al, 2004). Once in the CNS, the amoebae induce a strong inflammatory response with lysis of leukocytes that contributes to tissue damage (Cervantes-Sandoval et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Mice were separated into groups of 3 and killed at time periods of 24,32,48,72,96, and 120 hours postinoculation. No mice died before the end of the time periods studied (Jarolim et al 2000).…”
Section: Methodsmentioning
confidence: 99%
“…A condition similar to human PAM can be experimentally produced in mice when inoculated intranasally with N. fowleri (Duma 1972, Martinez et al 1973b). The primary pathway taken by N. fowleri from the nasal mucosa to the central nervous system (CNS) during the initial stages of PAM has been elucidated (Jarolim et al 2000). The possible involvement of the blood vessels and lungs in early stage dissemination of this rapidly fatal disease remains a question.…”
mentioning
confidence: 99%
“…PAM is an acute and rapidly fatal infection that is characterized by parasitic invasion of the central nervous system (CNS). The parasite gains access to the CNS by penetrating the olfactory neuroepithelium and migrating through olfactory nerves until it reaches the olfactory bulbs (Carter, 1970;Jaroli et al, 2002;Jarolim et al, 2000;Rojas-Hernández et al, 2004;Shibayama et al, 2003). Immunohistochemical studies of the early events of infection using a murine model have shown that the amoebae induce intense mucus secretion and an inflammatory reaction in the nasal cavity (Cervantes-Sandoval et al, 2008a;Rojas-Hernández et al, 2004).…”
Section: Introductionmentioning
confidence: 99%